Does antenatal depression predict post-partum depression and obstetric complications? Results from a longitudinal, long-term, real-world study - Luciano, Mario; Di Vincenzo, Matteo; Brandi, Carlotta; Tretola, Lucia; Toricco, Rita; Perris, Francesco; Volpicelli, Antonio; Torella, Marco; La Verde, Marco; Fiorillo, Andrea; Sampogna, Gaia (Frontiers in Psychiatry, 2022)
Background: Main aims of the present paper are to: 1) assess the prevalence of antenatal depression (AD) and identify its predictors; 2) analyse the impact of AD on obstetric outcomes and on the incidence of post-partum depression. Methods: All pregnant women referring to the Gynaecology and Obstetrics inpatients unit of the University of Campania “Luigi Vanvitelli” were invited to participate. Upon acceptance, women completed the Italian version of the Edinburgh Postnatal Depression Scale and an ad-hoc questionnaire on the women’s sociodemographic, gynaecological and peripartum characteristics as well as their psychiatric history. Women were assessed at each trimester of pregnancy, immediately after the childbirth and after one, three, six and eleven months. Results: 268 pregnant women were recruited, with a mean of 32.2 (±5.81) years. Ninety-seven women (36.2%) reported the presence of depressive symptoms during pregnancy. Predictors of AD were personal history of depression, a family history for depressive disorders and problematic relationships with the partner. The presence of AD was associated to a reduced gestational age at the time of delivery, a lower APGAR score at 1 and 5 minutes, labour induction and admission of the new-born into neonatal intensive care unit. Mothers with antenatal depression are less likely to natural breastfeed. Lastly, antenatal depression was a risk factor for higher EPDS scores at follow-ups. Conclusions: Our results support the idea that women should be screened during pregnancy and post-partum for the presence of depressive and anxiety symptoms. Health professionals should be adequately trained to detect psychiatric symptoms during pregnancy.